A puericultura no município de Belém-PA: o registro de ações da atenção primária à saúde no prontuário eletrônico do cidadão (PEC) do e-SUS - Ataide, Carlos Eduardo Ramos (2024)
The literature indicates great potential for children's development, especially in early childhood. However, to promote health in childhood, services and strategies are needed that are capable of monitoring the different stages of development. Childcare actions in the field of primary care enable disease prevention and early detection of children's health problems. One of the strategies developed in Brazil by the Ministry of Health is the Electronic Citizen Record (PEC). Objective: to investigate childcare actions in the municipality of Belém (Pará) based on SISAB data and information present and absent in the PEC. Method: descriptive-quantitative research, with a cross-sectional approach, used retrospective documentary analysis in order to analyze the PEC records in childcare consultations that took place in three basic health units in the municipality of Belém in the state of Pará. Results: Data from the Primary Care Health Information System (SISAB) allowed for the characterization of general childcare consultations in the municipality. Data collected from three basic health units in Belém (10%) regarding the filling in of information on childcare appointments in the citizen's electronic medical record indicates: (a) families seek out childcare appointments with a view to a scheduled appointment; (b) nursing is the professional category that most often provides this type of care; (c) together with nursing, medicine and occupational therapy are the three most prevalent professions. The profile of the children shows that consultations start after the 28th day of life, with follow-up visits varying between 3 months and 16 months. The areas that showed the most gaps were "phenotypic alterations", "risk factors", "referrals", "test requests", "test results", "medication prescriptions" and "scheduling appointments". On the other hand, the fields with the most records are mostly directly related to the physical examinations carried out by the professional at the childcare appointment and the birth data: "weight", "length", "up-to-date vaccination", "assessment", "objective" and "reason for appointment". Final considerations: For future studies, we suggest research that describes the physical conditions (e.g. presence of computers, access to the web; consultation time; dynamics of the records) and human resources training (courses, workshops) related to the investments made by the government to fill out the PEC.